2019
DOI: 10.5433/1679-0359.2019v40n6p2535
|View full text |Cite
|
Sign up to set email alerts
|

Shade nets and substrates in seedling production of Annona squamosa L. in the Roraima Cerrado

Abstract: Sugar apple (Annona squamosa L.) is one of the most widely grown member of the Annonaceae family in several regions, but there is still a lack of agronomic data regarding the management of its initial growth stages under Cerrado conditions. The aim of the present study was to evaluate the production of Annona squamosa L. seedlings under different environmental conditions achieved by using shade nets (E1: ChromatiNet® Silver 50%; E2: ChromatiNet® red 50%; E3: ChromatiNet® red 35%; E4: ChromatiNet® Silver 35%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Comparing only the environment using photo-converting mesh nets and considering the substrate that had the greatest increase in dry mass (S2), the experiment found that the accumulation of photo assimilates in collard green seedlings was directly associated with the color of the mesh and not with the level of shading. The silver-colored nets (A4 and A5) positively and proportionally influenced the accumulation of aerial and root biomass (Table 4), diverging from the results found by Sakazaki et al (2019) and by Monteiro et al (2022), who observed greater accumulation of ADM in environments with greater shading, and RDM in environments with less shading, regardless of color. Silva et al (2013) studied the growth of tomato seedlings on different nets with 50% shading and found no differences in root mass between the environments.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Comparing only the environment using photo-converting mesh nets and considering the substrate that had the greatest increase in dry mass (S2), the experiment found that the accumulation of photo assimilates in collard green seedlings was directly associated with the color of the mesh and not with the level of shading. The silver-colored nets (A4 and A5) positively and proportionally influenced the accumulation of aerial and root biomass (Table 4), diverging from the results found by Sakazaki et al (2019) and by Monteiro et al (2022), who observed greater accumulation of ADM in environments with greater shading, and RDM in environments with less shading, regardless of color. Silva et al (2013) studied the growth of tomato seedlings on different nets with 50% shading and found no differences in root mass between the environments.…”
Section: Resultsmentioning
confidence: 56%
“…Red-colored net meshes (A2 and A3) raised ambient temperature significantly, corroborating findings by Silva et al (2013) in environments utilizing nets of the same color. According to the authors, if the correct temperature management is not applied in these environments, adverse conditions can negatively influence plant production, even in species adapted to tropical conditions, as observed in the production of pine cone seedlings (Sakazaki et al, 2019), tomatoes (Monteiro et al, 2018) and pimenta-decheiro, a Brazilian chili pepper (Monteiro et al, 2022) in the savannah region of Roraima.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasize that the results obtained here are part of a framework of information compiled about the positive effect of these environments on the development of seedlings of some commercial species, such as: bell pepper -Capsicum annuum (MONTEIRO NETO et al, 2016), tomato -Solanum lycopersicum (MONTEIRO NETO et al, 2018) and ata -Annona squamosa (SAKAZAKI et al, 2019).…”
Section: Resultsmentioning
confidence: 89%
“…Although the records in the literature on the use of photoconverter screens in the production of seedlings of olerícola species are still scarce, especially to the culture of chili pepper, there are studies (HENRIQUE et al, 2011;SAKAZAKI et al, 2019) that indicate its use for horticultural production.…”
Section: Resultsmentioning
confidence: 99%